PERBANDINGAN TERAPI HIPERTENSI TERHADAP PENURUNAN TEKANAN DARAH PADA PASIEN PROLANIS DI PUSKESMAS KABUPATEN BANYUMAS WILAYAH TIMUR - Novi Istianah Azizah; Aziez Ismunandar; Tunjung Winarno (Prodi Farmasi Fakultas Sains dan Teknologi Universitas Peradaban, 2021)
Hypertension is one of the most common cardiovascular diseases and the most common in the community. Hypertension or known as high blood disease is a condition in which systolic blood pressure is more than 140 mmHg and diastolic blood pressure is more than 90 mmHg. The purpose of this study was to determine the comparison of hypertension therapy to lowering blood pressure in prolanis patients. This study used an analytic observational design with a cohort method. The data was collected retrospectively by looking at the patient's drug monitoring book and prescriptions. The population in this study was all hypertension prolanis participants at the Banyumas District Health Center in the East Region including the Sokaraja 1 Puskesmas, Kalibagor Puskesmas, Kemranjen 1 Puskesmas, Tambak 1 Puskesmas, Kebasen Puskesmas and Sumpuih Puskesmas 1. Sampling was carried out using total sampling. The sample in this study were 166 patients. The data analysis in this study used the Kruskal Wallis test. In the Kruskal Wallis the Asymp value was obtained. Sig. 0.060> 0.05, which indicates that there is no meaningful difference between hypertension therapy to lower or stabilize blood pressure. The single antihypertensive that is best in lowering or stabilizing systolic blood pressure is amlodipine. Meanwhile, the best combination antihypertensive in lowering or stabilizing systolic and diastolic blood pressure is the drug Amlodipine + Bisoprolol.